The Influence of Inquiry Learning on Concept Mastery Ability and Physics Problem Solving Ability of Students on Work and Energy Material - Dedi Sapriyadin; Sutopo Sutopo; Hari Wisodo (Jurnal Penelitian Pendidikan IPA, 2023)
The aim of the study was to determine differences in students' concept mastery abilities and students' problem solving abilities in the material of effort and energy using inquiry learning with students who learned using conventional learning as well as the correlation between concept mastery abilities and students' energy and effort problem solving abilities. This research is a quantitative research with a Quasi Experiment research design and the research design is a nonequivalent control group design. This study involved an experimental class that used the Inquiry learning model with learning stages according to the Inquiry learning model syntax and a control class that used conventional learning with learning stages according to the learning model used by the teacher when teaching. Taking the research sample using random sampling technique. The data collection instrument used tests with physics concept mastery skill instruments in the form of 10 multiple choice questions and 5 physics problem solving questions in the form of description questions. The test data were obtained through the pretest and posttest which were then subjected to prerequisite tests. The prerequisite test results stated that the data were normally distributed, homogeneous, and the test was linear. The data that has passed the prerequisite test is then used to test the hypothesis using Ancova. The results of the data analysis test showed that there were significant differences in students' concept mastery and problem-solving abilities between classes using Inquiry learning and classes using conventional learning. In addition, the results of the research data analysis show that there is a correlation between the ability to master the concept and the ability to solve problems, which means there is a relationship between the ability to master the concept and the ability to solve problems. The conclusion of the research shows that inquiry learning on work and energy materials can improve students' concept mastery and problem-solving abilities